2017
DOI: 10.1152/ajpheart.00399.2017
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the exercise pressor reflex in type 1 diabetic rats

Abstract: Previous studies have shown that diabetic peripheral neuropathy affects both unmyelinated and myelinated afferents, similar to those evoking the exercise pressor reflex. However, the effect of type 1 diabetes (T1DM) on this reflex is not known. We examined, in decerebrate male and female T1DM [streptozotocin (STZ)] and healthy control (CTL) rats, pressor and cardioaccelerator responses to isometric contraction of the hindlimb muscles during the early and late stages of the disease. STZ (50 mg/kg) was injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“… 29 Moreover, Grotle et al indicated that at 6 weeks after STZ treatment, the pressor and cardioaccelerator responses to contraction were significantly attenuated in diabetic rats, suggesting that afferent activity decreases to some extent. 30 Our experiments show that these diabetic rats exhibit mechanical allodynia at 6 weeks after induction ( Figure 2A , 4 weeks: P <0.05; 2, 4, and 6 weeks: P <0.01). This result is in agreement with the previous observation that Paulson et al reported.…”
Section: Resultsmentioning
confidence: 54%
“… 29 Moreover, Grotle et al indicated that at 6 weeks after STZ treatment, the pressor and cardioaccelerator responses to contraction were significantly attenuated in diabetic rats, suggesting that afferent activity decreases to some extent. 30 Our experiments show that these diabetic rats exhibit mechanical allodynia at 6 weeks after induction ( Figure 2A , 4 weeks: P <0.05; 2, 4, and 6 weeks: P <0.01). This result is in agreement with the previous observation that Paulson et al reported.…”
Section: Resultsmentioning
confidence: 54%
“…Both animal and human studies have shown that, in chronic diseases such as heart failure (20), hypertension (39), type 2 diabetes (29), and peripheral artery disease (14,55), blood pressure responses to exercise are exaggerated. We recently extended these findings to include the early stages of type 1 diabetes mellitus (T1DM) in rats (23). However, the underlying mechanisms contributing to the exercise pressor reflex dysfunction in T1DM are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic stimuli evoke the metaboreflex by stimulating primarily group IV afferent endings, whereas mechanical stimuli evoke the mechanoreflex by stimulating primarily group III afferent endings (26,35). Previous studies have shown that the exercise pressor reflex is exaggerated in cardiovascular-related diseases such as heart failure (36,50), peripheral artery disease (3,47), hypertension (2,32) and type-1 diabetes (16). Type-2 diabetes mellitus (T2DM) is also considered a cardiovascular-related disease, as individuals with T2DM are two-to fourfold more likely to die from a cardiovascular-related event than those without T2DM, an effect that, in turn, is associated with disease duration and severity (17,51).…”
Section: Introductionmentioning
confidence: 99%